A vector controlled matrix converter induction motor drive - Sünter, Sedat (1995)
This thesis concerns the design and construction of a closed-loop controlled matrix converter induction motor drive, using transputer parallel processors. The modulation algorithms used for the matrix converter are described. A 2.5 kW experimental matrix converter using IGBT switching devices has been constructed and tested. An analysis of the losses in the converter has been carried out and this gives good agreement with the measured losses.